Developmental validation of the Microreader Group Y Direct ID System: A novel six‐dye typing system with 54 Y‐chromosomal loci for forensic application. Issue 20 (3rd September 2022) - Song, Mengyuan; Jiang, Lanrui; Lyu, Qiang; Ying, Jun; Wang, Zefei; Zhou, Yuxiang; Song, Feng; Luo, Haibo; Song, Xingbo; Ying, Binwu
Abstract: Y‐chromosome, as a gender‐determined biological marker, is inherited only between fathers and sons. The Y‐chromosome short tandem repeats (Y‐STRs) play an essential role in paternity lineage tracing as well as sexual assault cases. The Microreader Group Y Direct ID System as a six‐dye multiplex amplification kit, including 53 Y‐STR and one Y‐Indel locus, would improve performance and aid in obtaining more information through a greater number of loci with high polymorphism. In the present study, to verify the accuracy and efficiency of the kit, developmental validation was conducted by investigating sensitivity, species specificity, PCR inhibition, male–male and male–female mixtures, and reproducibility. The kit was tested using 311 male samples from Han and Qiang populations in Sichuan Province. The results showed that this kit had fairly high power for forensic discrimination (Han: haplotype diversity [HD] = 1, Qiang: HD = 0.999944). Additionally, 44 confirmed father–son pairs were also genotyped, among which 69 distinct haplotypes could be obtained. These father–son pairs cannot be distinguished by commonly used Y‐STR panels, indicating that adding these extra Y‐STRs to a single panel can achieve better discrimination performance. Collectively, the Microreader Group Y Direct ID System is robust and informative for forensic applications.